Emergência e produtividade da cultura do milho em função de diferentes mecanismos de abertura de sulco - Kirch, Valdecir André (2019)
Corn crop managed under no-tillage system is successful in its establishment and development, and consequently its production related to sowing quality. Physical factors of the environment such as temperature, humidity and aeration are directly related to the type of groove opening mechanism, especially in areas with compaction problems. The aim of this study was to evaluate the effect of the use of different ridging mechanisms on the emergency and productivity of corn crop. The experiment was carried out under dryland conditions in an experimental area of the UFSM Department of Agronomic and Environmental Sciences, Campus of Frederico Westphalen, in 2015, in a dystrophic Red Latosol with 54% of clay. The experimental design used was a randomized complete block design (DBA) in a split plot scheme with four replications. The seven treatments evaluated were: absence of fertilizer furrower, 0.06 and 0.12 m depth lagged disc furrower, 0.06 and 0.12 m depth chisel furrower, both with plain cutting disk, corrugated cut disc and guillotine furrower depth of 0.06 and 0.12 m. Productivity, mobilized soil volume, plant emergence, plant tipping and root development were evaluated. Data were subjected to analysis of variance by the F test at a significance level of 5%. When treatment was significant, Tukey test (p < 0.05) was performed. The yield of corn crop was affected by the type of furrower mechanism, and the highest yields were obtained when using stalk mechanisms. The larger volume of soil mobilized by the use of furrower stems increased on the average time of corn emergence. The productivity of corn crop presents intermediate correlation with the volume of mobilized soil (r = 0,33) and a medium root diameter (r = 0,32). The corn cultivation, without furrower mechanism, in a compact direct planting system, tends to provide decrease under the crop productivity.